Effect of home‐based hot bathing on exercise‐induced adaptations associated with short‐term resistance exercise training in young men - Ryosuke Takeda; Tsubasa Amaike; Taichi Nishikawa; Kohei Watanabe (Physiological Reports)
Abstract This study investigated whether home‐based bathing intervention (HBBI) improve muscle strength gain and protect cardiovascular function by short‐term resistance training (RT). Thirty‐one healthy young men measured the maximum voluntary isometric contraction (MVC) of knee extensor, electrically evoked knee extension torque, and mean arterial pressure (MAP). Then, participants were divided into three groups with matching MVC: shower without bathing (control, n = 10), thermoneutral bathing (36°C‐bathing, n = 10), and hot bathing (40°C‐bathing, n = 11), and conducted 2 weeks of HBBI. Following familiarization for HBBI, participants completed 2 weeks of HBBI and acute RT (five sessions of three sets of 10 isometric knee extension at 60% MVC). Baseline neuromuscular and cardiovascular function was assessed again following completion of the 2 weeks of intervention. MVC was non‐significantly increased after the RT period in 40°C‐bathing with large effect size (partial η2 = 0.450). The electrically evoked knee extension torque (10/100‐Hz ratio) was significantly increased after the RT period in control (p = 0.020). MAP did not alter due to bathing intervention and RT (all p > 0.05). HBBI improved muscle strength without RT‐induced alteration of peripheral muscle condition. Shower without bathing reduced muscle strength gain but increased peripheral muscle condition. Short‐term RT does not adversely affect the cardiovascular function, regardless of HBBI.